AN ANALYSIS OF THE ROLE OF THE PRINCIPAL TO IMPROVE THE QUALITY OF SCHOOL MANAGEMENT AT SMP NEGERI 4 TOLITOLI - Rusdin, Diyenti (Jurnal Madako Education, 2021)
The purpose of this research was to analyze the role of the principal to improve the quality of school management. This research used descriptive qualitative design and it was conducted in SMP Negeri 4 Tolitoli. The technique of collecting data used interview and questionnaire, were the data obtained from the principal, five teachers and six students. The result of this research is the principal carrying out her role properly. The principal plays the role of educator, planner and implementer.